2012
DOI: 10.1002/cphc.201200664
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Complexes of Hydrogen with Helium

Abstract: High-resolution mass spectra of helium nanodroplets doped with hydrogen or deuterium reveal that copious amounts of helium can be bound to H+, H2+, H3+, and larger hydrogen-cluster ions. All conceivable HenHx+ stoichiometries are identified if their mass is below the limit of ≍120 u set by the resolution of the spectrometer. Anomalies in the ion yields of HenHx+ for x=1, 2, or 3, and n≤30 reveal particularly stable cluster ions. Our results for HenH1+ are consistent with conclusions drawn from previous experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
36
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 68 publications
6
36
1
Order By: Relevance
“…The computed evaporation energies show a steady decreasing tendency, changing from 0.7 to 0.4 kcal mol −1 when going from n = 3 to n = 6. This computational result is in contrast to the results of experimental MS studies [35,39] showing that n = 6 is a 'magic number' and HHe + 6 has pronounced stability (see also our own MS study in Section 2 supporting this statement). Classical and quantum dynamical studies have also been attempted on these systems [73].…”
Section: Introductioncontrasting
confidence: 95%
See 1 more Smart Citation
“…The computed evaporation energies show a steady decreasing tendency, changing from 0.7 to 0.4 kcal mol −1 when going from n = 3 to n = 6. This computational result is in contrast to the results of experimental MS studies [35,39] showing that n = 6 is a 'magic number' and HHe + 6 has pronounced stability (see also our own MS study in Section 2 supporting this statement). Classical and quantum dynamical studies have also been attempted on these systems [73].…”
Section: Introductioncontrasting
confidence: 95%
“…Despite the fact that the H x He + n molecular ions and their He-solvated complexes are formed by the two most abundant elements of our known universe, surprisingly little is known about the structure, energetics, and especially the nuclear dynamics of H x He + n species. Most of the experimental investigations, especially for larger x and (in particular) larger n values, are mass spectrometry (MS) studies [33][34][35][36][37][38][39]. MS does provide important information about the existence of H x He + n species (vide infra), and even some limited information about their relative stabilities.…”
Section: Introductionmentioning
confidence: 99%
“…A few years later, using polarised Gaussian orbitals, it has been confirmed that it is stable with a binding energy of about 100 cm −1 and it was predicted that this complex ion should be detectable below 140 K [60]. As already mentioned above, stable He n -H + x complexes have been found, first in a 4.4 K drift tube [45] and recently using He droplets [46]. But there are no spectroscopic studies at all and no state of the art calculations.…”
mentioning
confidence: 83%
“…Superfluid helium droplets provide a very cold environment (0.37 K) in which complexes of ions with He can be embedded. Using a highresolution mass spectrometer, a whole zoo of He n H + x and He n D + x ions has been identified recently [46]. However, neither of these experiments is capable to follow the dynamics of the growth of such ions.…”
mentioning
confidence: 99%
“…15,23 Here, n = 12 is a frequently observed anomaly, often interpreted to indicate formation of a solvation shell with icosahedral symmetry, 22,24 but the number of helium atoms in the first solvation shell may be much larger. For example, 18–20 atoms are needed to complete the first solvation shell for Mg + , 20,25 20 for I 2 + , 21 60 for C 60 + , and 62 for C 70 + .…”
Section: Introductionmentioning
confidence: 99%